2014
DOI: 10.1590/0001-3765201420130061
|View full text |Cite
|
Sign up to set email alerts
|

Trichostrongylus and Haemonchus anthelmintic resistance in naturally infected sheep from southern Brazil

Abstract: The anthelmintic resistance in small ruminants is a common problem and concern worldwide. The aim of this study was to verify anthelmintic treatment efficacy in naturally infected sheep. This study was conducted on nine herds that used the same anthelmintic management for over a year. In each farm, the animals were divided into two groups: untreated control group (n = 5) and treated (n = 10) according to the number of eggs per gram of feces (EPG). The treatment effect was checked based on EPG results and larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This study revealed multiple infections in cattle in the Adamawa region of Cameroon and this parasitism was similar to that already reported in cattle in many countries in Africa including Burkina Faso [22], Senegal [18] and Cameroon in small ruminants [9]. Similar results with the predominance of Haemonchus and Trichostrongylus genera were also obtained in sheep in Brazil by Klauck et al, [23]. The antagonistic variation between Trichostrongylus sp and Haemonchus could be due to ecological niche competition as the two parasites share the same habitat (abomasum) [24].…”
Section: Variation Of the Larval Population Of Strongylessupporting
confidence: 90%
“…This study revealed multiple infections in cattle in the Adamawa region of Cameroon and this parasitism was similar to that already reported in cattle in many countries in Africa including Burkina Faso [22], Senegal [18] and Cameroon in small ruminants [9]. Similar results with the predominance of Haemonchus and Trichostrongylus genera were also obtained in sheep in Brazil by Klauck et al, [23]. The antagonistic variation between Trichostrongylus sp and Haemonchus could be due to ecological niche competition as the two parasites share the same habitat (abomasum) [24].…”
Section: Variation Of the Larval Population Of Strongylessupporting
confidence: 90%
“…This method helps to reduce the parasitic burden in the animals, but it has some disadvantages, including the imminent emergence of anthelmintic resistance in the parasites (MÁRQUEZ-LARA, 2003;FORTES et al, 2013). This situation a serious problem to animal health because it diminishes the efficacy of anthelmintics, and new reports of anthelmintic resistance are being recorded every year (KLAUCK et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, high occurrence of multidrug resistance in 30 sheep flocks from São Paulo state was observed, and levamisole was the most efficient anthelmintic (Veríssimo et al 2012). Levamisole is an imidazothiazole widely used to control nematodes in ruminants (Fauvin et al 2010;Klauck et al 2014). So, the implementation of strategies to control gastrointestinal nematodes with levamisole to preserve its efficacy for longer periods is important, through developing and validating tests to detect resistance to levamisole.…”
Section: Introductionmentioning
confidence: 99%